The Biggest Modern Woman of the World: Canada as an Absent Spouse - Kamboureli, Smaro (Studies in Canadian Literature, 1991)
Susan Swan's The Biggest Modern Woman of the World is a novel that desires to be both postmodern/Victorian and fictional/ historical. Within the nineteenth-century framework of the novel, modernity exceeds traditional norms in order to include sexual and national politics. Modernity is configured allegorically as allegory suggests the semiotics of otherness, be it the otherness of discourse, gender, or nation. As a Canadian woman, Anna becomes an allegory, imaging the vast Canadian landscape. Susan Swan inscribes her historical other, Anna Haining Swan, within those historical gaps that denied Anna's modernity its full expression. The Freudian/Lacanian premise that anatomical difference figures sexual difference becomes an analogue of the Victorian ethos. Anna's modernity undoes the sexual and political codes of her life: her autobiographical text becomes the only space that can contain her desires.